Acquired and specific immunological mechanisms co-responsible for efficacy of polymer-bound drugs - Ríhová, B; Strohalm, J; Kubácková, K; Jelínková, M; Hovorka, O; Kovár, M; Plocová, D; Sírová, M; St'astný, M; Rozprimová, L; Ulbrich, K (Journal of controlled release, 2002)
We present data providing new evidence that poly[N-(2-hydroxypropyl)methacrylamide] (PHPMA)-bound drugs, unlike free drugs, have both cytostatic and immunomobilizing activity (CIA). Immediately after injection, due to the high level of the drug, the main activity of the polymeric conjugate is cytotoxic and cytostatic. Later on, long-term circulating PHPMA-bound drug, at concentrations lower than its minimal inhibitory levels, mobilizes the defense mechanisms of the host. Cytotoxic and cytostatic effects of drug-PHPMA were repeatedly confirmed. The following data support the concept of the immunomobilizing activity of the N-(2-hydroxypropyl)methacrylamide (HPMA) conjugates: (a) pre-treatment with free drugs (doxorubicin, cyclosporin A) accelerates the appearance of EL4 mouse T-cell lymphoma while a similar pre-treatment with doxorubicin-PHPMA induces limited but definitive mobilization of the host's defense mechanisms; (b) mice cured of EL4 mouse T-cell lymphoma, BCL1 mouse B-cell leukemia and 38C13 mouse B-cell lymphoma by injection of doxorubicin-PHPMA conjugate targeted with monoclonal antibodies (anti-Thy 1.2 for EL4, anti-B1 for BCL1 and anti-CD71 for 38C13) and re-transplanted with a lethal dose of the same cancer cells survive without any treatment considerably longer than control mice; (c) increased NK activity and anti-cancer antibody was detected only in animals treated with doxorubicin-PHPMA conjugate; and (d) considerably increased NK and LAK activity was seen in a human patient treated for generalized breast carcinoma with doxorubicin-PHPMA-IgG.
Keywords: myši; Methacrylates; Antibody-Dependent Cell Cytotoxicity; lékové transportní systémy; nádory prsu; Doxorubicin; Tumor Cells, Cultured; hemangiosarkom; Animals; protinádorové látky; Hemangiosarcoma; Mice; Drug Delivery Systems; Antineoplastic Agents; doxorubicin; methakryláty; buňky NK; Killer Cells, Natural; nádorové buňky kultivované; zvířata; Neoplasms, Experimental; Breast Neoplasms; buněčná cytotoxicita závislá na protilátkách; experimentální nádory